Life cycle assessment of butanol production - Brito, Marta (2019)
The goal of this work was to analyse and compare the environmental impacts of three production methods of butanol. The first one is based on the oxo synthesis and the others use ABE (acetone, butanol and ethanol) fermentation. A life cycle assessment for all alternatives under study was carried out. The ABE fermentation using corn as substrate presents the highest environmental impact and the ABE fermentation using wheat straw is the one that presents the lowest environmental impact, when the allocation method was based on mass. Considering an economic allocation method, the relative weight of butanol raised which increased considerably the environmental impact value in ABE processes due to the lower economic value of gases. A sensitivity analysis was performed for the production of butanol from the two ABE processes varying the data of lower quality to analyse how this would affect the environmental impacts. In the ABE process with wheat straw the variations performed within the scope of the sensibility analysis had no meaningful effect in the global impact (<4.0%) except when the production of gases was varied. In this case the reduction of 50% in the mass of gases produced could result in an increase of roughly 40% in the global impact. For the ABE process with the corn the variation of wastewater produced resulted in a decrease of global environmental impact lower than 1%.